Faktor-Faktor yang Mempengaruhi Harga Saham Blue Chip Periode 2019-2023 - Lailatul Maesyaroh; Ika Indriasari; Rita Meiriyanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Earning Per Share (EPS) on the stock prices of blue chip companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The method used in this study is a quantitative method with a multiple linear regression approach. The research sample was selected using purposive sampling, with the criterion being companies that consistently included in the LQ45 index during the research period. The analysis results show that ROA does not have a significant effect on stock prices, while DER has a significant negative effect on stock prices. Meanwhile, PER and EPS have a significant positive effect on stock prices. These findings imply that investors should consider the DER, PER, and EPS ratios in their investment decisions, while ROA is not a primary factor influencing blue-chip stock prices during the period.